Isolation and Synthesis of Misszrtine A: A Novel Indole Alkaloid From Marine Sponge-Associated Aspergillus sp. SCSIO XWS03F03 - Zhou, Rong; Liao, Xiaojian; Li, Hangbin; Li, Jing; Feng, Pengju; Zhao, BingXin; Xu, Shihai (Frontiers in Chemistry, 2018)
A novel indole alkaloid, Misszrtine A (1), was isolated from marine sponge-derived fungus Aspergillus sp. SCSIO XWS03F03. The planar structure of 1 was assigned by analysis of spectroscopic data, the absolute configuration of which was unambiguously determined by total synthesis. Compound 1 represents the first example of N-isopentenyl tryptophan methyl ester with a phenylpropanoic amide arm, which exhibited a potent antagonistic activity on HL60 (IC50 = 3.12 μM) and LNCaP (IC50 = 4.94 μM) cell lines. Bioactivity evaluation reveals that functional group on indole nitrogen of 1 has a great effect on its cytotoxity, which provides a mean to probe the structure-activity relationships of 1.